The first self-replicating molecule and the origin of life - Laos, Roberto (2014)
The origin of life on Earth is one of the most challenging questions in science. In the last 60 years, considerable progress has been made in understanding how simple molecules relevant to life can be generated spontaneously or are known to arrive to Earth from space. Additionally, analysis of the evolution history of nucleic acids, which are the repository of genetic information, points to a now extinct, universal common ancestor for all life on Earth. The studies of the origin of life offer many clues towards a common origin, perhaps not just on Earth but somewhere else in the solar system. However due to the length of time that the Earth has harbored life, the oldest clues of the first organisms are mostly gone. It is unlikely to find exactly what this first organism was like. Nevertheless, in the last few years, synthetic biology has made remarkable progress at modifying biomolecules, particularly nucleic acids. It is possible that soon we will be able to construct and understand a minimalistic system in which molecules can copy themselves in a protocell. The study of such systems could shed light into the origin of the first organisms.